Sexual & reproductive health information on minor consent forms for pubertal suppression and gender affirming hormones - Taylor, Julia; Vullikanti, Meesha; Nelamangala, Samhita L.; Boguszewski, Katherine E.; Marshall, Mary Faith (Frontiers in Reproductive Health, 2023)
Introduction Transgender and Nonbinary (TNB) youth need specialized sexual and reproductive health (SRH) information and counseling. One avenue for providing this information is the use of informed consent documents before initiating pubertal suppression (PS) and/or gender-affirming hormones (GAHs). This study aims to compare the type and amount of SRH information included on informed consent documents used across clinical sites providing PS and GAH to youth. Methods As part of a larger, IRB-approved survey on informed consent, providers of gender-related care to youth uploaded informed consent forms used in clinical practice. Publicly available forms were also included in analysis. Content analysis of these forms was undertaken using published clinical guidelines to inform coding and reflect the SRH implications of starting PS and GAH. Results 21 unique consent documents were included in the content analysis (PS = 7, Masculinizing = 7, Feminizing = 7). SRH information on consent documents fell into 4 broad categories: (1) changes in sexual organs and functioning; (2) pregnancy and fertility information; (3) cancer risk; and (4) sexually transmitted infections. Forms varied considerably in the level of detail included about these SRH topics and most forms included implicit or explicit acknowledgement of the uncertainty that exists around certain SRH outcomes for TNB youth. Conclusions There was substantial variability in both SRH content and context across consent forms. The role of consent forms in fostering TNB youth's understanding of complex SHR information when initiating PS and GAHs needs further clarification and development. Future research should focus on ways to ensure provision of adequate SRH information for TNB youth.